The social patterning of vicarious discrimination: Implications for health equity - Quinn, Edward B.; Ross, Jessica D.; Boston, P. Qasimah; Committee, HEAT Steering; Mulligan, Connie J.; Gravlee, Clarence C. (Social science & medicine (1982), 2023)
Most research on discrimination and health operationalizes discrimination as direct individual experiences. Here, we examine the social patterning of vicarious discrimination, an important but largely overlooked dimension of discrimination. Drawing on community-based participatory research with a multi-stage probability sample (n = 178) of African Americans in Tallahassee, Florida, we measured vicarious discrimination, or exposure to discrimination through one's family and friends. We used chi-square tests to examine gender differences in the social domains and relational sources of vicarious discrimination. Negative binomial regression models were fit to identify predictors of exposure to vicarious discrimination. Vicarious discrimination is more prevalent than direct experiences of discrimination (73 versus 61%) and more than 20% of participants report vicarious discrimination in the absence of direct discrimination. For women, vicarious discrimination most often involved the workplace; for men, police. However, gender differences are smaller for vicarious versus direct discrimination. Close friends and children were top relational sources of vicarious discrimination for men and women, respectively. Middle-aged participants reported the most vicarious discrimination. Overall, our data show that vicarious discrimination is more common than widely understood and associated with individual-level sociodemographic characteristics that index one's position in broader social systems. The prevalence of vicarious discrimination in the absence of direct discrimination suggests that standard approaches, which measure individual exposures in isolation, are subject to misclassification bias. Our results imply that existing research on discrimination and health, which already demonstrates substantial harm, underestimates African Americans' true exposures to salient aspects of discrimination. •Discrimination is associated with worse health outcomes.•Most studies of discrimination omit vicarious exposures to discrimination.•Twenty percent of participants reported vicarious but no direct discrimination.•Exposure to discrimination is underestimated in the health equity literature.•Future studies should account for exposure to vicarious discrimination.